2006
DOI: 10.1245/s10434-006-9172-z
|View full text |Cite
|
Sign up to set email alerts
|

Bypass Surgery Versus Palliative Pancreaticoduodenectomy in Patients with Advanced Ductal Adenocarcinoma of the Pancreatic Head, with an Emphasis on Quality of Life Analyses

Abstract: QoL analysis revealed favorable QoL data after DLB. Additionally, the survival rates of the two groups did not differ significantly, but morbidity and mortality rates in the PR group were elevated. Therefore, the use of PR for advanced pancreatic cancer needs to be carefully evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 27 publications
1
35
1
2
Order By: Relevance
“…23 The most common morbidity after double bypass is DGE of which incidence was up to 20%. 19 Lesurtel et al 6 reported that the position of gastrojejunostomy (antecolic or retrocolic) did not influence incidence of DGE after double bypass for unresectable pancreatic and periampullary cancer. The two RCTs showed that postoperative morbidity incidence rate was comparable between double bypass and biliary bypass alone.…”
Section: Perioperative Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…23 The most common morbidity after double bypass is DGE of which incidence was up to 20%. 19 Lesurtel et al 6 reported that the position of gastrojejunostomy (antecolic or retrocolic) did not influence incidence of DGE after double bypass for unresectable pancreatic and periampullary cancer. The two RCTs showed that postoperative morbidity incidence rate was comparable between double bypass and biliary bypass alone.…”
Section: Perioperative Outcomesmentioning
confidence: 99%
“…13 Outcomes Table 1 shows outcomes of biliary and gastrointestinal double bypass from the literature. 4,6,7,9,10,[14][15][16][17][18][19][20][21][22] Among the 14 studies, two were prospective randomized controlled trials (RCTs) comparing double bypass and biliary bypass alone, 14,15 eight studies were retrospective comparative studies 4,7,10,[16][17][18][19][20] and the remaining were case series. 6,9,21,22 A B …”
Section: Surgical Proceduresmentioning
confidence: 99%
See 3 more Smart Citations